OP0093 The Natural History of Thrombotic Events in Systemic Lupus Erythematosus and Associated Risk Factors. (9th June 2015) - Hickman, K.; Magder, L.; Petri, M.
Abstract : Background: Prospective cohort studies of the natural history of thrombosis in SLE, including events before diagnosis are rare. No previous study has identified risk factors prospectively for both venous and arterial thrombosis. Objectives: In this study we used a large prospective SLE cohort to assess the natural history of both arterial and venous thrombosis before and after the diagnosis of SLE. Methods: 2305 SLE patients were enrolled in a prospective cohort. Medical records were reviewed to identify the occurrence of arterial and venous thrombosis prior to cohort entry. During participation in the Lupus Cohort, arterial thrombosis was diagnosed by patient history, diagnostic enzymes tests and imaging, including arteriogram, and venous thrombosis by ultrasound, CT or venography. We calculated the rate of thrombosis per person-year in periods of follow-up defined by time since diagnosis with SLE. Results: The highest rates of both venous thrombosis and arterial thrombosis were observed in the 2 years before and the 2 years after diagnosis: 8.9-10.5 per 1000 patient years for arterial thrombosis and 11.4-12.5 per 1000 patient years for venous thrombosis. A second peak in incidence of arterial thrombosis (11.8 per 1000 patient years) was observed later in the course of SLE. Conclusions: This large cohort study indicated that prevention of both venous and arterial thrombosis is important around the time of diagnosis of SLE. Monitoring for thrombosis should occur throughout the disease course, being mindful of the arterial thrombosis risk with longer duration of SLE. Our results suggest that the mechanism of events before diagnosis is not accelerated atherosclerosis as suggested by some investigators. Accelerated atherosclerosis would not explain the increase in both arterial and venous events that occurs before and at diagnosis. Disclosure of Interest: None declared